2013
DOI: 10.3949/ccjm.80.e-s1.03
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes and lowering costs by applying advanced models of in-home care

Abstract: With advances in monitoring and telemedicine, the complexity of care administered in the home to properly selected patients can approach that delivered in the hospital. The challenges include making sure that qualified personnel regularly visit the patient at home, both individually and in teams; information is accurately communicated among the caregiver teams across venues and over time; and patients understand the information communicated to them by providers. Despite these challenges, the benefits of treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…To the knowledge of the authors, this is the first well‐designed, case–control study of HBPC for frail elders in the Medicare FFS arena. Potential confounders present in previous before‐and‐after comparison studies were adjusted for by providing a methodologically robust external control group . The large Medicare database and covariate adjustments addressed statistical challenges of selection bias and regression‐to‐the mean effects common in population‐based studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the knowledge of the authors, this is the first well‐designed, case–control study of HBPC for frail elders in the Medicare FFS arena. Potential confounders present in previous before‐and‐after comparison studies were adjusted for by providing a methodologically robust external control group . The large Medicare database and covariate adjustments addressed statistical challenges of selection bias and regression‐to‐the mean effects common in population‐based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical barriers to randomized controlled studies and difficulty identifying an adequate control group has limited research on HBPC programs. Prior observational research found that, over a 4‐year period, a posthospital house call program had aggregate costs that were 38% lower than for the 6 months before enrollment . Another study showed that individuals in an HBPC program were less likely to enter a hospital and had lower rates of ED and specialty care visits .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various benefits of incorporating HHC in the health system are known worldwide [6]. The services provided through HHC programs are different from country to country, but most programs are community-based, staffed mainly by professional nurses, and regulated by standard guidelines, which reflect the standard of care for all home health agency interactions [4].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Home-based medical care, which encompasses both primary and palliative care, provides a mechanism for such patients to obtain ongoing doi: 10 care in the community setting. 5 In home-based primary care, patients ideally receive comprehensive longitudinal primary medical care at home from an interprofessional team of physicians, nurse practitioners, or both, together with nurses, social workers, and skilled therapists. In some cases, all team members are employees of a given practice.…”
mentioning
confidence: 99%